Instrumentation Detailed Engineering (International Journal of Engineering and Computer Science, 2016)
Instrumentation Detailed Engineering (IDE) is a study which defines every technical and non technical aspects of project development. IDE follows Basic Engineering (BE) and Front End Engineering Design (FEED).  It contains in detail diagrams and drawings for construction, civil works, Instrumentation, Control System, Electrical Facilities, Management of Suppliers, Schedule of Activities, Costs, Procurement of Equipment, Economic Evaluation and also Environmental Impacts before starting of construction of a project. Instruementation detailed engineering found to be the best method for plant commissioning and plant maintainence.